2019
DOI: 10.1002/hep.30246
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Age and Comorbidity in a US Insured Population‐Based Cohort of Patients With Chronic Hepatitis B

Abstract: Insured CHB patients were older with more comorbidities and experienced higher incidence and prevalence of CKD and OF than controls. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
77
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 34 publications
10
77
1
Order By: Relevance
“…However, the addition of ETV for the treatment of CHB did not cause an interaction with HTN and DM and cause a further decline in renal function. This is an important finding as patients with CHB have been reported been noted to have an increase risk for the development of HTN and DM, but our results suggest that treatment with ETV should not be withheld over concern of hastening renal impairment in the presence of HTN and DM among patients with CHB . In addition, the proportion of patients in each subgroup that had a negative change in their renal function were not found to be significantly different among each other, findings which strengthen our suggestion that ETV should not be withheld as treatment for concern of renal function; however, renal function should be routinely monitored, and treatment individualized for each patient.…”
Section: Discussionsupporting
confidence: 80%
“…However, the addition of ETV for the treatment of CHB did not cause an interaction with HTN and DM and cause a further decline in renal function. This is an important finding as patients with CHB have been reported been noted to have an increase risk for the development of HTN and DM, but our results suggest that treatment with ETV should not be withheld over concern of hastening renal impairment in the presence of HTN and DM among patients with CHB . In addition, the proportion of patients in each subgroup that had a negative change in their renal function were not found to be significantly different among each other, findings which strengthen our suggestion that ETV should not be withheld as treatment for concern of renal function; however, renal function should be routinely monitored, and treatment individualized for each patient.…”
Section: Discussionsupporting
confidence: 80%
“…Within the US population, patients with CHB were found to have a higher Deyo‐Charlson Comorbidity Index compared with a nonmatched CHB group. Patients with CHB had a higher prevalence of alcoholism, cardiovascular disease, diabetes, hepatitis C virus, human immunodeficiency virus, and renal impairment . Interestingly, in a Taiwan‐based study, CHB was found to be associated with decreased risk for ischemic stroke, although this claims‐based study was unable to account for variables such as toxic habits and laboratory data …”
Section: Nonliver Comorbidities Of Chbmentioning
confidence: 93%
“…CHB has also been associated with a higher prevalence of malignancy, including colorectal, pancreatic, gallbladder and biliary duct, kidney, and ovarian cancer, as well as Hodgkin's lymphoma, non‐Hodgkin's lymphoma, and multiple myeloma . There has been some debate regarding the association of CHB and lymphoma .…”
Section: Nonliver Comorbidities Of Chbmentioning
confidence: 99%
See 2 more Smart Citations